ENHANCING PHOTOVOLTAIC POWER PREDICTION FOR SUSTAINABLE ENERGY FUTURES - Cempaka Amalin Mahadzir,; Ahmad Fateh Mohamad Nor,; Siti Amely Jumaat, (2024)
In an era where transitioning to sustainable energy sources is becoming increasingly important, Enhancing Photovoltaic Power Prediction for Sustainable Energy Futures explores the vital developments required to maximize solar power output. This book meticulously analyzes the methodologies and state of-the-art technology that improve solar power prediction accuracy and dependability. It comprises the difficulties in incorporating solar energy into conventional power systems and emphasizes the significance of predictive analytics in attaining energy sustainability by crossing the gap between theoretical models and real-world implementations. With an eye on the future, this research effort is an indispensable resource for scholars, professionals, and decision-makers who are dedicated to advocating renewable energy sources and creating a more environmentally friendly future for future generations.